Field‐Aligned Proton Beams Upstream of the Martian Bow Shock: First Observations - Meziane, K. (2025)
We report fast sunward-propagating energetic proton field-aligned beams (FABs) observed about one Mars radius upstream of the Martian bow shock, recorded by the Solar Wind Ion Analyzer instrument on the MAVEN spacecraft. The velocity distributions show that all the beams have a bulk parallel speed ${v}_{B}=(1.35pm 0.21)V_{S}$, exceeding the shock speed ${V}_{S}$. Several FABs are observed in the field-aligned region, linked to the quasi-parallel shock. The nearly synchronous variations of shock ${heta }_{Bn}$ values and beam speeds rule out specular reflection, suggesting a non-specular reflection mechanism. However, the slower Martian foreshock beam speeds remain unexplained compared to their terrestrial counterparts.